Efektivitas Promosi Kesehatan Metode Aktivitas Kreatif Menulis terhadap Penurunan Tingkat Kecemasan Remaja Boarding School Menjelang Ujian Akhir di Banda Aceh - Duana, Maiza; Nurdin, Ambia; Putri, Ermita Silvana; Sihombing, Eni Monaliska; Hafni, Idarul; Dessritina, Pesona Dessritina (Lembaga Teewan Journal Solutions, 2026)
Anxiety before final examinations is a common psychological problem among high school students and may negatively affect concentration, learning readiness, and academic performance. One strategy that can be used to reduce anxiety is expressive writing. This study aimed to analyze the effect of health promotion through expressive writing activities on anxiety levels among twelfth-grade boarding school students facing final examinations. This study employed a quasi-experimental design with a pretest-posttest control group approach. The sample consisted of 90 students, including 45 students in the experimental group and 45 students in the control group. Anxiety levels were measured using a 20-item DASS-like Anxiety questionnaire. Data were analyzed using Paired Sample t-test and Independent Sample t-test. The results showed that the mean anxiety score in the experimental group decreased from 39.53 to 15.93 after the intervention (p < 0.001). Furthermore, there was a significant difference in anxiety reduction between the experimental and control groups (p < 0.001). Expressive writing was found to be effective in reducing anxiety levels among students prior to final examinations..